PENGEMBANGAN SISTEM PENGELOLAAN SAMPAH DI KOTA PAREPARE - Sarbi, Sukaji (Bumi Lestari; Vol 8 No 1 (2008), 2012)
Waste is often viewed as a problem in human life. On one hand, waste is considered as having no economic value, thus disposed; on the other hand it is viewed as useful material. The purpose of this research was to develop a waste management system in Parepare. It was conducted in a region of 99.33 km2 consisting 21 villages. The location was determined on the basis of population density, resulting in the villages of: Wattang Soreang, Labukang, and Lumpue. The primary data was obtained from 100 respondents, and the secondary data from various related institutions. The respondent profile shows that 87.0 % respondents are males and 13.0 % females. In terms of education level, around 11.0 % respondents are of elementary schools, 23 % of junior secondary schools, 52 % of senior high schools, and 14.0 % of tertiary education. 64.0 % respondents are state civil servants and National Army, 15.0 % self-employed, 12.0 % farmers and fishermen, and 9.0 % laborers. At present, the waste management system is not optimal because of limited vehicles of waste removal, field workers, and waste collecting facilities, thus only as much as 256 m3/day .
Keywords: Waste management with 3 R + 1P pattern going to zero waste